SDRs, interest, and the aid link - WILLIAMSON, J. (PSL Quarterly Review, 2013)
One probable consequence of the Dollar crisis is the initiation of an attempt to effect a major reform of the international monetary system. The agenda for any future discussions on reform is bound to be long and varied. The present article, rather than providing a comprehensive survey of all the issues, focuses on the relationship between two of the proposed reforms that appears to have escaped attention up to now. The author considers the proposal to make the SDR the basic reserve asset in the system and the proposal for an “aid link”. It is argued that for the monetary success of SDRs it is important that they pay competitive interest rates, thus reducing the value of seignorage that could be distributed to less-developed countries through an aid link. However, there is no reason why the remaining seignorage should not be distributed on aid-link principals. JEL: E42, F33, F35